Calf diseases at Jhenaidah district, Bangladesh: Epidemiological status with relation to age and season - Biplob Kumar Sarker,; Md Shah Alam, (Research in Agriculture Livestock and Fisheries, 2023)
In Bangladesh calves are affected by several types of diseases and most of them are parasitic, infectious, metabolic or nutritional, surgical affection etc. causing severe economic losses in every year. The study was conducted to investigate the epidemiological status of calves’ diseases with relation to age and seasonal variation at Jhenaidah district, Bangladesh. A total of 12525 clinical cases were registered in all 6 Upazila of Jhenaidah district for the clinical diagnosis and therapeutic purposes during a period of two years, which were analyzed to evaluate the prevalence of clinical diseases in calves. Each of the clinical case was diagnosed on the basis of history, general examination, physical examination and clinical findings. Among the recorded cases the highest prevalence of clinical cases in calves were found to be round worm infestation ( 14.80%), and followed in descending order by non-specific diarrhoea ( 9.20 %), liver fluke infestation ( 8.34%), anorexia ( 7.95%), lice infestation ( 6.66%), debility (6.42%), wounds (4.68 %), tick infestation (3.93 %), tape worm infestation (3.54%), non-specific fever & navel ill (3.42%), coccidiosis (3.35%), conjunctivitis (3.16%), FMD (2.83%), pneumonia (2.49%), allergy/skin disease (2.30%), coldness (2.06%), tympany/bloat (1.71%), calf-scour (1.61%) etc. Among the general clinical disorder, the highest prevalence of clinical cases was non-specific diarrhoea (9.20%), among parasitic disease the highest prevalence was round worm infestation (14.80%), among infectious disease the highest prevalence was coccidiosis (3.35%), among surgical affection the highest prevalence was wound (4.68%). The influence of age and season on the occurrence of these diseases was considered. Immuno prophylaxis and hygienic management should be introduced to curtail the prevalence of calf diseases and disorders. So more epidemiological and intensive laboratory study should be needed to confirm the etiology, prevention and control measures of the diseases and disorders in cattle at the study area. Res. Agric. Livest. Fish. Vol. 10, No. 2, August 2023: 189-197